(untitled) (Proceedings of the International Conference on Future of Education, 2019)
English is a global language at present and it is considered the key to knowledge, information, communication, technology, travel, trade and business and is used as the medium of instruction in most higher education institutes and universities in Asia (Turmapang, 2012). Being equipped with the right speaking skills and knowledge in the language boost the chance for employment opportunities in undergraduates. However, majority show reticence towards English ‘speaking’ even as graduates. There is a great unwillingness to engage in public speaking in English and communication outside the classroom. With this as the main research problem, the aim of this research is to find out effective Communicative Task-Based Activities (CTBA) which can be used in each sphere in the Blooms Taxonomy, to improve speaking confidence in undergraduates. A mixed approach was incorporated into the study. 32 Sri-Lankan undergraduates in the first year were selected as the sample based on purposive sampling and were monitored and taught for a period of one academic semester (15 weeks) based on CTBA. According to Blooms Taxonomy(1956), initial activities were designed for small groups and later the group numbers were gradually reduced to promote autonomous/ independent speaking skills in students. The CTBA was divided into pre, during and post-task phases. SPSS was utilized to quantitatively analyze the data. Thematic content analysis was followed to analyze the interviews. In conclusion, it was revealed that speaker autonomy can be achieved with the correct use of Blooms Taxonomy by incorporating CTBAs correctly at each level in the 6 spheres. Keywords: CTBA, Confidence, Blooms Taxonomy, Autonomy